Peranan Pendidikan Berbasis Kearifan lokal dalam Pembelajaran di Sekolah - Ni Made Suarningsih (Jayapangus Press, 2019)
Education more broadly has the role of civilization, the civilization in question is to further improve the quality of human beings, which in the end becomes advanced and civilized human beings. Therefore school assignments, especially teachers to be able to improve the learning process to achieve national education goals through various learning models. In this case, local wisdom is very suitable to be used as a learning platform Local wisdom can not be separated from culture. This paper discusses (1) Local cognitive-based education (2) The Role of Local Wisdom-Based Education in School Learning (3) Impact of Local Wisdom-Based Education for Teachers, Students and Schools. Local wisdom-based education is the implementation of learning that provides a view of life, science, and various life strategies in the form of activities carried out by local communities to answer various problems in meeting their needs. The impact of local wisdom-based education for teachers, students and schools is as a medium to preserve the potential of each region, thus creating learning that respects regional cultural diversity